Cofactor F420, an emerging redox power in biosynthesis of secondary metabolites. (28th February 2022) - Bashiri, Ghader
Abstract : Cofactor F420 is a low-potential hydride-transfer deazaflavin that mediates important oxidoreductive reactions in the primary metabolism of archaea and a wide range of bacteria. Over the past decade, biochemical studies have demonstrated another essential role for F420 in the biosynthesis of various classes of natural products. These studies have substantiated reports predating the structural determination of F420 that suggested a potential role for F420 in the biosynthesis of several antibiotics produced by Streptomyces . In this article, we focus on this exciting and emerging role of F420 in catalyzing the oxidoreductive transformation of various imine, ketone and enoate moieties in secondary metabolites. Given the extensive and increasing availability of genomic and metagenomic data, these F420 -dependent transformations may lead to the discovery of novel secondary metabolites, providing an invaluable and untapped resource in various biotechnological applications.